Investigation of various commercial PEDOT:PSS (poly(3,4-ethylenedioxythiophene)polystyrene sulfonate) as a hole transport layer in lead iodide-based inverted planar perovskite solar cells - Alishah, Hamed Moeini; Choi, Fatma Pinar Gokdemir; Gunes, Serap (SPRINGER, 2021)
Inverted-type perovskite solar cells have drawn remarkable attention due to solution-processable, straightforward configuration, low-cost processing, and manufacturing at very high throughput, even on top of flexible materials. The hole transport material (HTM) plays a vital role to achieve high performance in inverted type of perovskite solar cells. Herein, we report on the effect of different commercial PEDOT:PSS such as PH 1000, PH 500, P VP AI, and P T2, on the performance of CH3NH3PbI3-based planar perovskite solar cells.
Keywords: HIGH-PERFORMANCE; HIGHLY EFFICIENT; GRAPHENE OXIDE/PEDOTPSS; DEPOSITION; CATHODE; FILMS; CRYSTALLIZATION; NANOCRYSTALS; TEMPERATURE; POLYMER; Engineering; Materials Science; Physics